An uphill hurdle to education: the experiences of housing insecure and homeless students in a Southern California community college - Bitanga, Bert Malasig (My University, 2026)
The number of students who experience housing insecurity and homelessness (HIH) across the nation has reached disconcerting levels, revealing the problem’s pervasiveness. In particular, more community college students experience the phenomena compared to their peers at 4-year institutions. The purpose of this study was to explore the experiences of housing insecure and homeless students before, during, and after admission to a southern California community college. The study aimed to illuminate the experiences that influenced the students’ access to higher education and academic persistence. The trauma–informed care model was the theoretical framework and Tinto's (1993) model of student departure was the conceptual framework used to guide this study. The methodology chosen was generic qualitative research consisting of semistructured interviews with seven housing insecure and homeless students from a southern California community college. The research findings of this study were organized by themes arranged under the study’s research questions. The themes included: (a) Traumatic Experiences, (b) Anxiety and Distress, (c) Matriculation Restriction, (d) Delay of Higher Education, and (e) Resiliency. The findings indicated various forms of early childhood experiences, including HIH, presented traumatic and adverse challenges for the study participants before enrolling in a community college. Additionally, participants continued encountering various roadblocks, but others maintained resiliency throughout their matriculation process and college experience.
Keywords: Trauma; Housing insecurity; Homelessness; Trauma-informed care; Tinto's 1993 model of student departure; Resiliency